Efficacy and Safety of Peroral Endoscopic Myotomy for Sigmoid-Type Achalasia: A Systematic Review and Meta-Analysis - Xu, Jin; Zhong, Chunyu; Huang, Shu; Zeng, Xinyi; Tan, Shali; Shi, Lei; Peng, Yan; Lü, Muhan; Ma, Lianjun; Tang, Xiaowei (Frontiers in Medicine, 2021)
Background: The efficacy and safety of peroral endoscopic myotomy (POEM) in the treatment of sigmoid-type achalasia is unknown. This meta-analysis aims to explore the clinical outcomes of POEM for sigmoid-type achalasia. Method: We searched all relevant studies published up to September 2020 in Pubmed, Embase and Cochrane library databases. Meta-analyses for clinical success, Eckardt score, angle of esophageal tortuosity, diameter of esophagus, lower esophageal sphincter (LES) pressure, integrated relaxation pressure (IRP), adverse events and gastroesophageal reflux diseases were performed based on random or fixed-effects models as needed. Results: We found a total of eight studies that provided data on 248 patients. Overall, the pooled clinical success was achieved in 211 sigmoid-type achalasia patients (90.4%; 95% confidence interval [CI], 85.5%-93.8%). The pre- and post-POEM Eckardt scores, angle of esophageal tortuosity, diameter of esophageal, LES pressure and IRP were significantly improved (All P<0.05). The pooled adverse events rate was 13.0% (95% CI, 3.6%-37.4%). The pooled objective confirmation of reflux rate was 41.5% (95% CI, 26.5%-58.3%) and symptomatic reflux rate was 12.5% (95% CI, 8.3%-18.4%). Conclusions: Our current evidence indicated that POEM is an effective and safe therapeutic modality for the treatment of sigmoid-type achalasia.